Peran Guru dan Orang Tua dalam Mendukung Pembelajaran Anak Tuna Rungu di Sekolah Luar Biasa (SLB) PGRI Kamal, Bangkalan - Sukesih Siallagan; Nova Estu Harsiwi (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2024)
Deaf children's learning in elementary schools faces various challenges that require special support from teachers and parents. This article examines the important role of teachers and parents in helping deaf children learn. Data was collected through direct observation in class and in-depth interviews using qualitative case study methods. The research results show that special training for teachers and good collaboration between teachers and parents are very influential in improving the quality of education for deaf children.